HP PRIME: product of research in Mathematics Education. - Springer, G.T. (2016)
The development of the HP Prime graphing calculator and wireless classroom was aided significantly by a core group of mathematics educators who advised the development team and a pedagogical architect who sat on the team. This paper reflects back on the design decisions they made and the research basis that shaped at least some of those decisions.